Ressonância magnética do trato córtico-espinhal de pacientes com acidente vascular cerebral submetidos à reabilitação fisioterapêutica - Lugokenski, Ricardo (2015)
The aim of this study was to evaluate the effects of two rehabilitation methods in stroke patients, being a conventional one and another using games, over the corticospinal tract degeneration, measured through Magnetic Resonance (MR) Tractography. The tested hypothesis was that game-based rehabilitation would bring additional benefits to the patients, especially in motor improvement. This is an experimental quantitative, case-based study, with 32 rehabilitation sessions, and MR evaluations before and after rehabilitation, by two independent readers. The scientific production 1 shows the obtained results. The neuronal integrity measurements showed superior values for the game-based rehabilitation group, for both readers, although the differences were not statistically significant. The results suggest that game-based rehabilitation may be superior to conventional rehabilitation, but further studies are needed to confirm these findings